IDENTIFICATION OF INFLUENZA VIRUSES IN HUMAN AND POULTRY IN THE AREA OF LARANGAN WET MARKET SIDOARJO-EAST JAVA, INDONESIA - Frederika, Edith; Mareta, Aldise; Poetranto, Djoko; Wulandari, Laksmi; Setyoningrum, Retno Asih; Setyowati, Lucia Landia; Yudhawati, Resti; Soegiarto, Gatot; Yamaoka, Masaoki (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: Influenza is a viral infection that attacks the respiratory system (nose, throat, and lungs) that commonly known as "flu”. There are 3 types of influenza viruses, such as type A, type B, and type C. Influenza virus type A is the type of virus that can infect both human and animals, virus type B are normally found only in human, and Influenza virus type C can cause mild illness in human and not causing any epidemics or pandemics. Among these 3 types of influenza viruses, only influenza A viruses infect birds, particularly wild bird that are the natural host for all subtypes of influenza A virus. Generally, those wild birds do not get sick when they are infected with influenza virus, unlike chickens or ducks which may die from avian influenza. Aim: In this study, we are identifying the influenza viruses among poultry in Larangan wet market. Method: Around 500 kinds of poultry were examined from cloacal swab. Result: Those samples were restrained with symptoms of suspected H5. The people who worked as the poultry-traders intact with the animal everyday were also examined, by taking nasopharyngeal swab and blood serum. Conclusion: Identification of influenza viruses was obtained to define the type and subtype of influenza virus by PCR.